Surgical Outcomes and Patient Satisfaction With the Low-Cost, Semi-Rigid Shah Penile Prosthesis: A boon to the Developing Countries. Issue 4 (16th July 2021) - Krishnappa, Pramod; Tripathi, Amit; Shah, Rupin
Abstract: Introduction: In developing countries most patients with refractory erectile dysfunction cannot afford a penile prosthesis (PP) due to its cost and non-coverage by insurance companies. Aim: To assess the patient satisfaction outcomes with a novel, low-cost, semi-rigid PP. Methods: 52 patients who had received the Shah semi-rigid PP between January 2013 and December 2018 were included in this bidirectional study. Patient demographics including age, etiology, body mass index, length of PP received and post-operative complications were recorded. Patient satisfaction with the PP was evaluated using the modified Erectile Dysfunction Inventory of Treatment Satisfaction (EDITS) Questionnaire. Main outcome measures: The primary outcome measures were overall satisfaction, total EDITS and mean EDITS score. The secondary outcome measures were residual penile tumescence, ease of concealment and post-operative complications. Results: The mean age of the patients was 38.79 years (25–68). Overall satisfaction (EDITS Q-1) of 4 (0–4) was reported by 84.62% (44/52) of patients. There was no significant difference ( P > .7) in the total EDITS and overall satisfaction based on various etiological factors. The mean EDITS scores (0–100) were 95.67 ± 10.76, 95.53 ± 8.46 and 91.72 ± 22.42 in 52 patients with BMI <25, 25–29.9 and >30 kg/m2 respectively. During sexual arousal after PP implantation, 26 (50%), 17 (32.7%) and 9 (17.3%) patients noted "good", "some" or "no" residual penile tumescence respectively. 47 (90.4%), 4 (7.7%) and 1 (1.9%) patients reported "good", "fair" and "poor" concealment respectively. In the prospective group, major and minor post-operative complications were seen in 10.7% (3/28) and 21.4% (6/28) of patients respectively. Conclusion: The semi-rigid Shah PP is a safe, effective and affordable option to treat patients with refractory ED. The ability to remove 1 or both sleeves in the Shah PP helps achieve a good fit with a small inventory. Krishnappa P, Tripathi A, Shah R. Surgical Outcomes and Patient Satisfaction With the Low-Cost, Semi-Rigid Shah Penile Prosthesis: A boon to the Developing Countries. Sex Med 2021;9:100399.